2019
DOI: 10.1111/jai.13969
|View full text |Cite
|
Sign up to set email alerts
|

Development of 28 EST‐SSR markers based on transcriptome sequences of Gobiobotia filifer and cross‐species amplification

Abstract: Gobiobotia filifer is a small benthic fish distributed in Yangtze River Basin. The abundance of G. filifer increased after impoundment of Xiluodu Dam and Xiangjiaba Dam. The state of population structure and changes of genetic diversity before and after impoundment of Xiluodu Dam and Xiangjiaba Dam were interesting issues. However, efficient molecular markers were rare, which will limit us to solve above problems. Twenty‐eight expressed sequence tag SSRs (EST‐SSRs) were successfully identified and verified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Moreover, the Ne, I, He, and PIC of Core Hunter 3 were higher than those of the breeding population, indicating that the alternative core collections had higher genetic diversity. We compared the quality of the core collections constructed by the two software programs and found that a comparison is more convincing than a core collection constructed by a single method [48,49]. Therefore, in this study, we adopted alternative core collections constructed by Core Hunter 3, which includes more extreme individuals of the breeding population, resulting in more abundant genetic diversity and better representation of the breeding population's genetic variation.…”
Section: Construction Of Core Collectionmentioning
confidence: 99%
“…Moreover, the Ne, I, He, and PIC of Core Hunter 3 were higher than those of the breeding population, indicating that the alternative core collections had higher genetic diversity. We compared the quality of the core collections constructed by the two software programs and found that a comparison is more convincing than a core collection constructed by a single method [48,49]. Therefore, in this study, we adopted alternative core collections constructed by Core Hunter 3, which includes more extreme individuals of the breeding population, resulting in more abundant genetic diversity and better representation of the breeding population's genetic variation.…”
Section: Construction Of Core Collectionmentioning
confidence: 99%